Subclinical hypocalcemia in dairy cows: reproductive and economic impacts on Eastern European farms - Berean, Daniel Ionut; Bogdan, Liviu Marian; Cimpean, Raluca (Frontiers in Veterinary Science, 2025)
IntroductionThis study investigated the association between postpartum subclinical hypocalcemia (SCHC) and reproductive and economic performance in dairy cows. SCHC is often overlooked yet may contribute significantly to reduced productivity and profitability in dairy herds.MethodsA total of 312 cows, Holstein Friesian and Romanian Spotted breeds, from three commercial farms in Eastern Europe were monitored during the first 60 days postpartum. Blood calcium levels were measured to classify cows into SCHC and normocalcemic groups.ResultsThe incidence of SCHC was 42.9%, with multiparous cows more frequently affected. Cows with SCHC had longer service periods, extended calving intervals, and required more artificial insemination attempts than normocalcemic cows. Although milk yield did not differ significantly between groups, SCHC cows exhibited moderately higher mastitis incidence and somatic cell counts, especially within the first 30 days postpartum. These factors contributed to increased indirect costs. Economic analysis indicated that SCHC cows incurred approximately 54 EUR more in additional costs per animal compared to normocalcemic cows.DiscussionSCHC is a hidden contributor to economic losses in dairy operations, primarily due to its negative impact on reproductive performance and udder health. These findings underscore the importance of early detection and preventive strategies to mitigate the effects of SCHC and improve herd productivity during the transition period.